Standing and Position of Islamic Law as Science in the Context of the Philosophy of Science (Study on the Tree of Rene Descartes Philosophy and the Loops of Knowledge Scheme of Gerald M. Edelman) - Adhiputro Pangarso Wicaksono (Activa Yuris: Jurnal Hukum, 2022)
This study aims to find out the standing and position of Islamic law as a science in the context of the philosophy of science. Research conducted with normative method resulted in the finding that in Rene Descartes's philosophical tree scheme, Islamic law, in this case is that the Qur'an and Hadith (As-Sunnah) are “rainwater” that provides the source of life for the philosophical tree. The “rainwater” enters the soil and then "absorbed" by the roots of metaphysics to then grow the stems of physics that branch into various sciences and fruits that are useful for human life as the purpose of Islamic law itself. Meanwhile, in the loops of knowledge scheme of Gerald M. Edelman, Islamic law as a science is included in the study of culture in sub-actions and societies because in principle Islamic law is sourced from the Qur'an and Hadith (As-Sunnah) is a way of life for human beings to act and behave and establish relationships with fellow human beings and society as Allah says in the Qur'an and the Hadith of the Prophet Muhammad